UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM MURID DENGAN MODEL PEMBELAJARAN JIGSAW DI KELAS V SDN 21/III KOTO PATAH TAHUN PELAJARAN 2015/2016 - Rawina Rawina (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2017)
This study aims to improve the learning process and student learning outcomes by using a jig saw on the subjects of Islamic religious education in class V SDN 21 / III Koto Patah. This type of research is a classroom action research with research subjects graders of SDN 21 / III Koto Broken totaling 24 people. The object of this research is the implementation and the results obtained from the application of methods jig saw. Data collection techniques used were observation and tests. Data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that the implementation of learning with jigsaw models can enhance the learning process and the learning outcomes of students in grade V SDN 21 / III Koto Patah. Improved learning model pupil activity jigsaw in the first cycle of 56.04% increased in the second cycle to 74.29%. The average value of student learning outcomes obtained in the first cycle of 65.58 increased to 76.67 in the second cycle. Pupils who reach a value ? 65 on the first cycle as many as 11 people or 45.83%. In the second cycle increased to 22 oarng or 91.67%. Thus, learning with jigsaw models on the subjects of Islamic religious education can be used in class V SDN 21 / III Koto Patah.